Research on building a set of criteria to evaluate the effectiveness of environmental protection management of Vietnam’s natural heritage sites - Thi Thanh An, Nguyen; Phung Van Khoa; Kieu Thi Duong; Phi Dang Son; Do Anh Tuan; Bui Chinh Nghia; Nguyen Quoc Hieu; Hoang Thi Thanh Nhan; Nguyen Thanh Vinh; Tran Thi Kim Tinh; et al. (Journal of Forestry Science and Technology, 2025)
Developing a set of criteria to evaluate the effectiveness of environmental protection management of natural heritage sites is extremely necessary in the context that Vietnam’s heritage sites are facing many risks and are increasingly degrading. The set of criteria was researched and developed specifically for natural heritage sites, which are proposed conservation areas based on data collection results at two natural heritage sites, Bach Ma National Park and Than Sa - Phuong Hoang Nature Reserve. The main methods used in this study include the method of inheriting domestic and foreign research documents combined with the Delphi method through 3 rounds of interviews based on quantitative assessment results through statistical values and experiences of a group of 20 experts including scientists working at research agencies, policy-making agencies, and managers of conservation areas. Through the process of eliminating and supplementing the results based on statistical values and opinions of the expert group, a set of criteria and indicators was formed. The set of criteria and indicators consists of 2 parts (1) Basic information table; (2) Evaluation criteria and indicators table including 35 criteria based on 5 management activities. Each criterion has 4 answers corresponding to points from 0 to 3 options for answers a to d.